Benchmarking as an instrument of marketing decisions - Skryhun, Natalya; Kolodiuk, Svitlana (My University, 2020)
Practical principles of benchmarking weight as marketing instrument of influence on strategic decisions of business development are studied in the article. Peculiarities of application and place of the tool are revealed and substantiated from ensuring competitiveness in the marketing portfolio. There is the procedure of benchmarking, and subsequent benchmarking of the received strategic data about the positive or negative experience of the competitor, which significantly affects its competitiveness is considered. У статті досліджено практичні принципи бенчмаркінгу як маркетингового інструменту впливу на стратегічні рішення розвитку бізнесу. Виявлені та обґрунтовані особливості застосування та місце використання інструменту із забезпечення конкурентоспроможності у маркетинговому портфелі. Розглянуто процедуру бенчмаркінгу та доведено необхідність проведення порівняльного оцінювання отриманих стратегічних даних про позитивний чи негативний досвід конкурента, що суттєво впливає на його конкурентоспроможність.
Keywords: кафедра маркетингу; конкурентоспроможність; бенчмаркінг; бенчмаркінг; маркетингова розвідка; стратегічні дані; competitiveness; benchmarking; marketing intelligence; benchmarking; strategic data